The Invisible Thread: The Influence of Liberal Faculty on Student Political Views at Evangelical Colleges. Issue 3 (2nd July 2016) - Hunt, Emily; Davignon, Phil
Abstract: This analysis examines the influences of family background and faculty political views on student political views at Evangelical colleges and universities. While the college-effects literature confirms that student interaction with faculty, peers, and the institution challenges pre-existing perspectives, many American Evangelical colleges are conservative and often reinforce rather than challenge mainstream Evangelical beliefs. Results from this analysis suggest that Evangelical colleges and universities with a greater percentage of liberal faculty influence students to become more liberal, even when accounting for the generally conservative upbringing of students. The net result of a more liberal "invisible thread" is a press against the right-leaning partisanship of American Evangelicalism.